2019 IEEE/ACM International Conference on Connected Health: Applications, Systems and Engineering Technologies (CHASE) 2019
DOI: 10.1109/chase48038.2019.00020
|View full text |Cite
|
Sign up to set email alerts
|

Health Monitoring in Smart Homes Utilizing Internet of Things

Abstract: In recent years the concept of the Internet of Things (IoT) has evolved to connect commercial gadgets together with the medical field to facilitate an unprecedented range of accessibility. The development of medical devices connected to internet of things has been praised for the potential of alleviating the strain on the modern healthcare system by giving users the opportunity to reside in the home during treatment or recovery. With the IoT becoming more prevalent and available at a commercial level, there ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…This study identified a limitation related to the distance threshold (20 m) between the body-attached sensors and the server receivers, and the greater distance, the more data loss. Alnaggar et al (2023) (Linkous et al, 2019). Adib et al (2015) utilized ubiquitous sensing technologies to remotely monitor vital signs using a wireless sensing technology called Vital-Radio, achieving a high accuracy of 99% for breathing and heart rate measurements.…”
Section: Related Workmentioning
confidence: 99%
“…This study identified a limitation related to the distance threshold (20 m) between the body-attached sensors and the server receivers, and the greater distance, the more data loss. Alnaggar et al (2023) (Linkous et al, 2019). Adib et al (2015) utilized ubiquitous sensing technologies to remotely monitor vital signs using a wireless sensing technology called Vital-Radio, achieving a high accuracy of 99% for breathing and heart rate measurements.…”
Section: Related Workmentioning
confidence: 99%
“…Nearables are also able to form ad hoc networks to allow them to collaborate, extending the range of in-home localization services for patients. This was discussed in the context of the AAL (20%) [54,58,59] and dementia care studies (6%) [60][61][62].…”
Section: The Application Of Sensors and Actuators Within Environmentsmentioning
confidence: 99%
“…6% Indoor localization. [16,57,58,[60][61][62]64] AAL for elderly patients living independently at home was often discussed in conjunction with fall detection [53,54,82]. General physiological and psychological well-being was a wider category that featured sensor and actuator combinations that applied to less common medical conditions.…”
Section: %mentioning
confidence: 99%